PENINGKATAN KETERAMPILAN KOLABORASI MELALUI MEDIA QUESTION AND ACT CARD BERBASIS CULTURALLY RESPONSIVE TEACHING PADA MATERI INDONESIAKU KAYA BUDAYA - kartika nirmalasari; Yuniawatika; Lilyana abiba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Collaboration skills are a collaborative skill aimed at solving a problem through combining many ideas. Collaboration skills are very important to learn, but in fact, the facts in the field state that there are still problems in this skill, some students are still unable to carry out discussion or collaboration activities well, therefore a media is needed that can be a card game called question and act cards based on the CRT approach or cultural responsiveness. Through the application of question and action cards, it can be seen that there is an increase in students' collaboration skills which is carried out for 2 cycles